The Necessity of Redefining and Presenting a New Perception on the Comprehensive Interpretation of the Holy Quran - Ghazipour, Saeed (2021)
The Holy Quran is an infinite ocean which benefits everyone to the extent of their scientific ability and scope of existence. This divine book would not be only a text; rather, its interpretation and explanation open various chapters of science, wisdom, and knowledge to human beings. Therefore, the only way to enter this gate of science, wisdom, and knowledge is its interpretation. Up to now, various approaches and interpretive books have been emerged to decipher and decode this divine blessing, but non of them has been perfect, and each is considered as a defect. Therefore, the best and the safest way would be to refer to a new definition of the “comprehensive” interpretation. In the following research paper, we will try to express the need and necessity of applying a comprehensive approach to the interpretation of the Holy Quran, providing a new definition of it in the description of the divine words.